UMA ABORDAGEM PARA INTEGRAÇÃO DE FERRAMENTAS PARA APOIO AOS PROCESSOS DO NÍVEL G DO MPS.BR - Castro, Thales Castelo Branco de (2009)
Facing a highly competitive market, companies are more and more concerned about obtaining certifications/assessments that provide evidence on the maturity of their software processes. Software tools play a relevant role in this context, but they can also increase the cost of process implementation due to their high acquisition costs. Specifically for small and medium companies, the adoption of the national reference model, MPS.Br, and the use of free tools is recommended in order to diminish costs. However, the usage of stand-alone tools make the process execution difficult, because it is often necessary to entry the same information in several tools. The goal should therefore be to integrate a set of tools that support the software development and maintenance processes in a company, creating a software development environment. In order to do so, it s necessary both a process that supports the selection of such tools and a model that determines the information to be shared by them. This model is expected to be used as an inter-language between different tools. This dissertation aimed at defining a process to guide the assessment and selection of free tools, and constructing ontologies that specify the information requirements for attending the level G of MPS.BR. The effective implementation of the proposed ontologies was considered as future work. The resulting infra-structure supports small and medium companies in reaching level G of MPS.Br and represents an important step towards the integration of free tools based on ontologies